Frequency of Iron Deficiency Anemia in Children Presenting with Febrile Fit - Fatima Ashraf; Habibullah Babar; Shaheen Ahmed; Naseem Khalid Shahwani; Khadija Rabnawaz; Maryam Anis; Sana Ullah Kakar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The purpose of this study is to estimate the percentage of children with IDA in febrile convulsions attending Bolan Medical Complex Hospital, Quetta. In this cross sectional study, an attempt will be made to identify the correlation between IDA and febrile convulsions in children. Methods: A cross-sectional study was conducted to determine the prevalence of iron deficiency anemia (IDA) in 150 children aged 6 months to 5 years with febrile seizures at Bolan Medical Complex Hospital Quetta. Data was collected through structured questionnaires, including demographic, clinical, and nutrition history details. Participants were selected based on age and presentation features. Seizure characteristics, dietary recall, and breastfeeding practices were also assessed. Parents provided informed consent before participation. One hundred and fifty children, between the age of 6 months and 5 years were participated in the study. Blood hemoglobin, serum ferritin, serum iron, and total iron-binding capacity were analyzed. Results: IDA was present in 45% of those children who had febrile seizures at point of this study. Also, IDA was linked to a higher incidence of complicated febrile seizures; 40 percent of IDA patients had had a complicated Febrile seizure compared with non-IDA 15 percent. Conclusions: The study brings attention to the need of routine checks of iron deficient acutely in pediatric patients with febrile seizures. Improving nutrition might perhaps prevent febrile seizures or even lessen their intensity. Keywords: Proportion of children, hemoglobin, serum ferritin, serum iron, nutritional deficiencies